Post-Material Aesthetics: A Conceptualization of Digital Objects. (3rd March 2020) - Folkmann, Mads Nygaard
Abstract: The article conceptualizes the ontology and aesthetics of digital objects. In the context of the article, digital objects are defined as designed objects that incorporate and employ digital technology. They include such products as smartphones, tablet computers and smart speakers, among others. The main point made in the article is that digital technology is changing object design. Digitization has created a new ontological constitution of objects that are simultaneously material and digital and whose function often relies on their connection to other objects via wireless technologies. Building upon this point, the article proposes a concept of post-material aesthetics which comprehends the ontological constitution of digital objects in relation to materiality, function and conceptual values. Employing the concept of post-material aesthetics, the article investigates how digital objects, in their particular constitution, impose new conditions for framing human experience.